Experimental study of multi-pass solar air thermal collector system assisted with sensible energy-storing matrix - Kareem, M.W. (Elsevier Ltd, 2022)
Analysis of heat transfer around the components of multi-pass solar air heating collector and its performance enhancement has been presented using experimental approach. Radiation and convection heat transfer from the system covers and collector plate to the flowing airstreams in the collector system have been investigated. Geological porous matrix has been used as thermal energy reservoir. Test rig was set up under daily average solar insolation, ambient temperature, wind speed, and relative humidity of 302.40 Wm-2, 29.30 Â°C, 0.58 msâ1, and 48.53, respectively. Thermal performance evaluation of the multi-pass solar air collector has been conducted in accordance with the ASHRAE standard specified for the solar air heating systems. Thermal collector efficiency range of 51.91â72.55 has been achieved with an optimum air mass flow rate of 0.013 kgsâ1. System evaporative capacity range of 1.158Ã10â3 - 1.205Ã10â3 kgsâ1 was computed. The matrix has extended the span of system operation for more than 3 h after sunset. Comparison of the outcome of multi-pass solar collector performance with the reported study has been done with good agreement. However, an improvement in performance through heat transfer from collector to the flowing air could be achieved. Â© 2022